Case Study: The Application of Extracorporeal Shockwave Therapy (ESWT) and Active Finger Blocking Exercise on Movement and Function of Fingers Disorders Caused by Trigger the 4th Finger Dextra - Juliastuti jujuk; Angie Destriani Nasution; Roihana Baintan; Ika Guslanda Bustam; Dwi Herdayanti (Jurnal Inspirasi Kesehatan, 2023)
Background: Trigger finger also referred to as stenosing tenosynovitis. It is a traumatic condition that involves the formation of nodules in the tendons of flexor digitorium muscle due to a combination of repetitive finger movements or local trauma and impaired healing, as a result of which the affected finger is locked in either a flexed or extended position thereby impeding movement. Objective: This case study was aimed to determine the effect of extracorporeal shockwave therapy, and active finger blocking exercise in one women patient, aged 47 years old with diagnosed of trigger the 4th finger dextra. Methods: This case studies have been carried out 6 times for 2 weeks in one women patient, by evaluating the degree of pain by using the Visual Analogue Scale (VAS), Joint Range of Motion (RoM) by using a goniometer and functional activity ability hands with the Disability of the Arm, Shoulder and Hand (DASH) questionnaire. Results: There was a decrease in the motion pain degree from VAS 7 to VAS 4, and the degree of tenderness pain from VAS 5 to VAS 2. There was an increase active flexion-extension movement of the 4th finger dextra from (S)=25°-0°-50° to (S)=40°-0°-75°, while passive movement from (S)=30°-0 °-60° to (S)=40°-0°-75°. There was a decrease in the value of hand disabilities based on the results of the DASH questionnaire from 24% to 21%. Conclusion: The application of extracorporeal shockwave therapy and active finger blocking exercise can reduce the pain, increase the range of motion and functional abilities patient diagnosed Trigger the 4th Finger condition.